2019
DOI: 10.3390/nu11092067
|View full text |Cite
|
Sign up to set email alerts
|

Thrombomodulin and Thrombopoietin, Two Biomarkers of Hemostasis, Are Positively Associated with Adherence to the World Cancer Research Fund/American Institute for Cancer Research Recommendations for Cancer Prevention in a Population-Based Cross-Sectional Study

Abstract: A pro-coagulative state is related to increased risk of cardiovascular diseases but also certain cancers. Since experimental and smaller human studies suggest that diet, physical activity, and body weight may all affect coagulation, we evaluated associations between these lifestyle factors and hemostatic biomarkers in a population-based study. Cross-sectional baseline data from 2267 randomly selected participants of EPIC-Heidelberg (age range 35–65 years) was used. Fibrinogen, glycoprotein IIb/IIIa, P-selectin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…A cross-sectional study reported that an increasing adherence to the WCRF/AICR recommendation decreased the incidence of metabolic syndrome, [47] whereas another study observed that it was associated with higher serum levels of thrombomodulin and thrombopoietin that might increase the CVD risk. [48] To our knowledge, this is the rst prospective cohort study reported the association between the WCRF/AICR lifestyle score and CVD risk although the analyses demonstrated nonsigni cant associations.…”
Section: Discussionmentioning
confidence: 75%
“…A cross-sectional study reported that an increasing adherence to the WCRF/AICR recommendation decreased the incidence of metabolic syndrome, [47] whereas another study observed that it was associated with higher serum levels of thrombomodulin and thrombopoietin that might increase the CVD risk. [48] To our knowledge, this is the rst prospective cohort study reported the association between the WCRF/AICR lifestyle score and CVD risk although the analyses demonstrated nonsigni cant associations.…”
Section: Discussionmentioning
confidence: 75%
“…Previous studies on the association between greater adherence to the WCRF/AICR lifestyle score and the CVD risk factors were limited and they yielded inconsistent findings. A cross-sectional study reported that an increasing adherence to the WCRF/AICR recommendation decreased the incidence of metabolic syndrome 50 , whereas another study observed that it was associated with higher serum levels of thrombomodulin and thrombopoietin that might increase the CVD risk 51 . To the best of our knowledge, this is the first prospective cohort study that reported the association between the WCRF/AICR lifestyle score and CVD risk, although the analyses demonstrated nonsignificant associations.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis of observational studies demonstrated that the adherence to WCRF/AICR recommendations reduced risks of cancer incidence and mortality in breast, lung, upper aerodigestive tract, stomach, prostate, and colorectal cancers [ 151 , 152 , 153 ], and they also improved hemostatic factors implicated in chronic disease development [ 154 ]. A special note on fiber intake and mortality should be made: there is an inverse association between fiber intake from foods and risk of death for respiratory diseases, infection, and cardiovascular diseases [ 155 ].…”
Section: Non-pharmacological Strategies To Reduce Cardiovascular Ementioning
confidence: 99%